2014
DOI: 10.1152/jn.00513.2013
|View full text |Cite
|
Sign up to set email alerts
|

A novel optic flow pattern speeds split-belt locomotor adaptation

Abstract: Finley JM, Statton MA, Bastian AJ. A novel optic flow pattern speeds split-belt locomotor adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Over several minutes of split-belt walking, interlimb parameters such as step length symmetry and double support time adapt (Reisman et al, 2005). Step length symmetry adaptation is a robust finding replicated in stroke survivors (Reisman et al 2007; Reisman et al 2013), Parkinson’s disease patients (Roemmich et al 2014a; Roemmich et al 2014b), and many conditions in healthy subjects (Malone, Bastian, 2010; Torres-Oviedo, Bastian, 2012; Torres-Oviedo, Bastian, 2010; Finley et al, 2014). During split-belt walking, ground reaction forces (GRF) exhibit predictive changes at initial contact, although vertical GRF in single support and propulsive GRF changes immediately, indicating reactive control (Mawase et al, 2013; Ogawa et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Over several minutes of split-belt walking, interlimb parameters such as step length symmetry and double support time adapt (Reisman et al, 2005). Step length symmetry adaptation is a robust finding replicated in stroke survivors (Reisman et al 2007; Reisman et al 2013), Parkinson’s disease patients (Roemmich et al 2014a; Roemmich et al 2014b), and many conditions in healthy subjects (Malone, Bastian, 2010; Torres-Oviedo, Bastian, 2012; Torres-Oviedo, Bastian, 2010; Finley et al, 2014). During split-belt walking, ground reaction forces (GRF) exhibit predictive changes at initial contact, although vertical GRF in single support and propulsive GRF changes immediately, indicating reactive control (Mawase et al, 2013; Ogawa et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…When individuals are initially exposed to walking with the belts moving at different speeds, step length asymmetry is magnified, and asymmetries are observed in both the spatial and temporal domains 12,1416 . This initial increase in asymmetry provides a stimulus driving individuals to recalibrate their motor commands in a feed-forward manner to reduce asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Also the visual inputs provide vital information for helping people to modify the walking pattern (Finley, Statton & Bastian, 2014). Some studies have demonstrated that children with DCD may rely more C Palomo-Nieto, M.; Psotta, R.; .…”
Section: Introductionmentioning
confidence: 99%